Tingkat Pengetahuan PUS Tidak Berhubungan dengan Keikutsertaan KB di Desa Argomulyo, Sedayu, Bantul Yogyakarta - Ardhiyani Muslimah; Nur Indah Rahmawati (Alma Ata University Press, 2014)
Family Planning (FP) participation is the most important thing in the family planning program in Indonesia. Based on the baseline study, family planning participations in 6 in Argomulyo village covered 533 couples (59.22 %) of 900 total couple of reproductive age. Knowledge is one of the factors that causes reproductive age couples to join the family planning program. Knowledge is used as the basis of actions to solve problems and this was the result of knowing after the people recognice an object. Knowledge about family planning is expected to cause the participation of reproductive age couples in the family planning program. The purpose of this study was to analyze the relationship between the knowledge level of family planning participation in reproductive age couples in Argomulyo village, Sedayu, Bantul, Yogyakarta 2014. Study design was observational analytic with cross sectional aproach. Technique sampling used was total sampling of reproductive age couples in Argomulyo village, Sedayu, Bantul, Yogyakarta resulted on 907 respondents. Data was colected by interview using the questionnaire. The analysis used was chi-square. The result of chi-square test showed a p-value 0.318>(0.05) and coefficients contingency of 0.05 so knowledge level had no relationship with FP participation. Knowledge level was 71.00% good, while the highest participation of family planning in the majority of with fair level enough was 68.8%, in addition, the highest proportion of couples who did not participate in FP program was 41.8%. In Conclusion, there was no significant relationship between the knowledge level about family planning and the participation of the family planning in reproductive age couples in Argomulyo village, Sedayu, Bantul, Yogyakarta year 2014.